2015
DOI: 10.3389/fmicb.2015.00774
|View full text |Cite
|
Sign up to set email alerts
|

Impact of surface structure and feed gas composition on Bacillus subtilis endospore inactivation during direct plasma treatment

Abstract: This study investigated the inactivation efficiency of cold atmospheric pressure plasma treatment on Bacillus subtilis endospores dependent on the used feed gas composition and on the surface, the endospores were attached on. Glass petri-dishes, glass beads, and peppercorns were inoculated with the same endospore density and treated with a radio frequency plasma jet. Generated reactive species were detected using optical emission spectroscopy. A quantitative polymerase chain reaction (qPCR) based ratio detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…While on polypropylene granules, 10 min of treatment yielded spore reductions by about 5 log 10 , the maximum spore inactivation on wheat grains was 3 log 10 units after 60 min of treatment (Butscher et al ). Hertwig et al () reported about a significantly lower sporicidal ( B. subtilis ) action of CAP on peppercorns compared to flat glass or spherical glass beads. This was explained by the more complex surface structure of peppercorns which is characterized by cracks, grooves and pits, which might cause shadow effects for the different generated components of the plasma (Hertwig et al ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While on polypropylene granules, 10 min of treatment yielded spore reductions by about 5 log 10 , the maximum spore inactivation on wheat grains was 3 log 10 units after 60 min of treatment (Butscher et al ). Hertwig et al () reported about a significantly lower sporicidal ( B. subtilis ) action of CAP on peppercorns compared to flat glass or spherical glass beads. This was explained by the more complex surface structure of peppercorns which is characterized by cracks, grooves and pits, which might cause shadow effects for the different generated components of the plasma (Hertwig et al ).…”
Section: Discussionmentioning
confidence: 99%
“…The sporicidal action of different CAP systems has been demonstrated with different setups (Boudam et al 2006;Bourke et al 2017;Hertwig et al 2018). It is well accepted that the highest sporicidal effect can be achieved when spores are directly exposed to the plasma discharge (Moisan et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NTP technology is considered efficient and economically viable as a result of its relatively low operating cost and energy consumption, with actual or potential applications with respect to inactivating microorganisms on foods such as almonds, fresh produce, food processing equipment and food handling environments, as well as in heat‐sensitive packaging materials, pharmaceuticals and medical devices . Because of its efficiency and ease for implementation, non‐thermal atmospheric pressure plasma, with different configurations and discharge gases, has been the focus of recent studies investigating the inactivation of spores …”
Section: Introductionmentioning
confidence: 99%
“…are typically reduced 4 to 6 logs by several minutes of treatment by different types of plasma systems (15)(16)(17)(18)(19)(20)(21)(22). The mechanisms of spore killing by plasma are complex (18), as UV photons, charged particles, electric fields, and reactive oxygen species (ROS) (e.g., ozone, atomic oxygen, and hydroxyl radicals if water is present) are all involved in spore killing (16,17).…”
mentioning
confidence: 99%